1990
DOI: 10.1172/jci114920
|View full text |Cite
|
Sign up to set email alerts
|

Increased hydrolysis of cholesteryl ester with prostacyclin is potentiated by high density lipoprotein through the prostacyclin stabilization.

Abstract: Prostacyclin (PGI2) has been reported to stimulate activities of acid cholesteryl ester hydrolase (ACEH; EC 3.1.1.13) and neutral cholesteryl ester hydrolase (NCEH; EC 3.1.1.13) in the smooth muscle cells leading to a decrease in intracellular cholesteryl ester. Recently, we have found that the half-life of PGI2 was prolonged through stabilization by HDL. HDL is known to have anti-atherogenic properties, although its precise mechanism has not been fully clarified. We therefore hypothesized that HDL can exert a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…80 Apart from bovious antiatherosclerotic acute effects of PGI 2 , such as synergism with NO in antiplatelet and fibrinolytic actions, its pathophysiologic antagonism with TXA 2 and its "cytoprotective" action, there are also chronic effects of PGI 2 that are involved mainly with metabolism of cholesterol and lipoproteins. Firstly, PGE 1 decreases influx of low density lipoproteins (LDL) into arterial walls in vivo, 81 secondly PGI 2 through cyclic AMP stimulates cholesteryl ester hydrolysis within smooth muscle cells in vitro, 82 and this effect of PGI 2 is potentiated by high density lipoproteins (HDL) 83 through stabilization of PGI 2 by HDL. 84 In patients with myocardial infarction or unstable angina pectoris, the stabilization of PGI 2 by HDL-associated apolipoprotein A-1 is impaired.…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…80 Apart from bovious antiatherosclerotic acute effects of PGI 2 , such as synergism with NO in antiplatelet and fibrinolytic actions, its pathophysiologic antagonism with TXA 2 and its "cytoprotective" action, there are also chronic effects of PGI 2 that are involved mainly with metabolism of cholesterol and lipoproteins. Firstly, PGE 1 decreases influx of low density lipoproteins (LDL) into arterial walls in vivo, 81 secondly PGI 2 through cyclic AMP stimulates cholesteryl ester hydrolysis within smooth muscle cells in vitro, 82 and this effect of PGI 2 is potentiated by high density lipoproteins (HDL) 83 through stabilization of PGI 2 by HDL. 84 In patients with myocardial infarction or unstable angina pectoris, the stabilization of PGI 2 by HDL-associated apolipoprotein A-1 is impaired.…”
Section: Atherosclerosismentioning
confidence: 99%
“…84 In patients with myocardial infarction or unstable angina pectoris, the stabilization of PGI 2 by HDL-associated apolipoprotein A-1 is impaired. 84 In summary, PGI 2 fortified by NO 85 might serve as an antithrombotic and antiatherosclerotic shield because of its platelet-suppressant, fibrinolytic cytoprotective, 86 antiproliferative, 71,87 antidegenerative and cholesterol-clearing 82,83 properties. Angiotoxicity and atherogenicity of cholesterol oxides are partially explained by the inhibition of PGI 2 synthase.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Recently, IP receptor activators were shown to suppress inflammation-induced vascular leak, likely due to the engagement of the cAMP/ EPAC/ Rap1 pathway. The lability of PGI 2 due to autohydrolysis is inhibited by HDL association (17). Indeed, we found that purified A1M nanodiscs can associate with Iloprost, a stable PGI 2 analog (42) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…ApoA1 also enhances endothelial-derived nitric oxide (NO) secretion, which promotes blood flow(15, 16). In addition, HDL suppresses thrombosis by enhancing the activity of prostacyclin (PGI 2 ) and attenuation of tissue factor expression(15, 17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…ApoA1 also enhances endothelial-derived nitric oxide (NO) secretion, which promotes blood flow ( 11 ). In addition, HDL suppresses thrombosis by enhancing the activity of prostacyclin (PGI 2 ) and attenuation of tissue factor expression ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%